Erratum - Skarlatou, Sophie (2021)
(Cell Reports 31, 107741-1–107741-14.e1–e4; June 9, 2020) In the originally published version of this article, three experiments were not described in the STAR Methods section. These were the preparation of isolated spinal cords, the analysis of fictive locomotion data, and three-dimensional positional analysis. These experiments have now been described in the article online. In addition, Talpalar et al. (2011) was added to the reference list and is cited in the newly added text. The authors regret this error.